2014
DOI: 10.1111/cen.12502
|View full text |Cite
|
Sign up to set email alerts
|

Identifying subgroups of obesity using the product of triglycerides and glucose: the Korea National Health and Nutrition Examination Survey, 2008–2010

Abstract: These data highlight the value of the TyG index in discriminating those subjects with higher risks of metabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 35 publications
4
47
0
Order By: Relevance
“…The TyG index value in the present investigation is in agreement with the majority of the reported adult literature , but higher than some others . Some investigators calculated the TyG index as a function of the log rather than the Ln (natural log) , which would explain the different numerical value for the index.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The TyG index value in the present investigation is in agreement with the majority of the reported adult literature , but higher than some others . Some investigators calculated the TyG index as a function of the log rather than the Ln (natural log) , which would explain the different numerical value for the index.…”
Section: Discussionsupporting
confidence: 90%
“…The baseline TyG index was significantly higher in those who developed diabetes vs. those who did not. Moreover, the incidence of diabetes increased in proportion to the TyG index quartiles, with a fourfold higher risk of diabetes in the highest vs. the lowest quartile . Lastly, the predictive power of TyG index was better than the TG/HDL ratio or the HOMA‐IR .…”
Section: Discussionmentioning
confidence: 95%
“…Notably, the cut-off point of 8.5 was quite different from the finding of 4.58 by Simental-Mendia [7], the reason for this may be explained by the different metabolic status among subjects from the two studies or the different ethnicities. The TyG level in our study was similar to that of other population from Korea [27, 32], America [33], France [30], and Spain [26], whereas the level of TyG in studies from Mexico was close to that of participants from Italy [31]. We also found that the diagnostic accuracy of TyG was superior to ALT, even if the optimal cut-off point of ALT was 20.5 U/L with a sensitivity of 66.1% and specificity of 65.9%.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of some studies revealed that there is a strong relationship between hypertriglyceridemia and the risk of Type 2 diabetes (16)(17)(18), however, the studies on its relationship with GDM is so restricted, especially in Middle Eastern mothers. This study aimed to clarify the association of serum levels of triglycerides during the 1st trimester with the risk of developing GDM.…”
Section: Introductionmentioning
confidence: 99%